RETRACTED: GATA4 Regulates Inflammation-Driven Pancreatic Ductal Adenocarcinoma Progression - Jiang, Weiliang; Chen, Congying; Huang, Li; Shen, Jie; Yang, Lijuan (Frontiers in Cell and Developmental Biology, 2021)
Cancer-associated inflammation is a key molecular feature in the progression of pancreatic ductal adenocarcinoma (PDAC). GATA4 is a transcription factor which participates in regulation and normal development of several endoderm and mesoderm-derived tissues such as the pancreas. Nevertheless, whether GATA4 functions in the inflammatory stimuli associated with pancreatic cancer progression is yet to be verified. In this research, we employed quantitative reverse transcription PCR, immunohistochemistry, and differential expression to investigate the association between GATA4 and inflammation-driven PDAC. We found that GATA4 was overexpressed in tumor tissues and this was accompanied by an increased level of inflammatory macrophages. We used macrophage-conditioned medium to validate inflammation models following treatment with varying concentrations of lipopolysaccharide and explored if GATA4-dependent inflammatory stimuli have effects on pancreatic cancer cell invasion and growth in vitro. Nude mouse models of dibutyltin dichloride-induced chronic pancreatitis with orthotopic tumor xenografts were used to in vivo evaluate the inflammatory microenvironment effect on GATA4 expression. The results indicate that overexpression of GATA4 dramatically aggravated inflammatory stimuli-induced pancreatic cancer cell invasion and growth via NF-κB and STAT3 signaling, whereas silencing of GATA4 attenuated it. Overall, the current results suggest that inflammation-driven cancer progression is dependent on GATA4 expression through the STAT3 as well as NF-κB signaling pathways.